STRATEGI PENGELOLAAN KEBUN BINATANG BANDUNG DALAM MENGHADAPI TANTANGAN NEW NORMAL - Suherlan, Afifa Magfhira; Ilham, Rizky Muhammad; Warlina, Lia (Majalah Ilmiah UNIKOM, 2020)
Bandung has many tourist attractions and can educate the public when visiting the Bandung Zoological Garden (BAZOGA) or also known as the Bandung Zoo. The zoo is one of the ex-situ conservation institutions that must pay attention to animal welfare by meeting all minimum welfare standards. This conservation area is located in the Coblong sub-district and has an area of 13 hectares and the diversity of animals in it. The function of the zoo that provides various types of trees in urban areas can be the lungs of the city. The purpose of this study is to find out what strategies to deal with the new normal at Bandung Zoo. The research method used is to collect primary and secondary data. Primary data were obtained by direct observation of the Bandung Zoo. The analytical method used in this research is a SWOT analysis. The results of this study are the identification of the potential and problems of the Bandung Zoo. Potentials owned by the Bandung Zoo include: (1) the existence of several new animal collections, namely native African animals, (2) a new bird aviary area that allows tourists to interact directly with birds. The weaknesses of the Bandung Zoo are: (1) ticket sales have not been made online or computerized, (2) there are still many empty reptile animal collections, (3) food courts are temporarily closed during the New Normal era. The strategy to manage Bandung Zoo tourism in the New Normal period as follows. First, ticket purchases are available using an online ticket booking system or online or computerized ticket buyer. Secondly, the management creates the reptile area so that it will increase knowledge in animal knowledge and add to the collection of animals in the Bandung Zoo. Thirdly the zoo applies a non-cash payment system and regulates seating positions in the foodcourt area. Key Words : New Normal, SWOT, Zoo